Setting up and running a small meat or fish processing enterprise - Fellows, Peter; Axtell, Barrie (Technical Centre for Agricultural and Rural Cooperation, 2003)
This book covers products that can be manufactured by small-and medium scale enterprises. Products such as canned meat and fish... or frozen meals are not included, as the technologies are expensive and demand production on a very large scale level.